2022
DOI: 10.1093/genetics/iyac086
|View full text |Cite
|
Sign up to set email alerts
|

Fine-tuning acetyl-CoA carboxylase 1 activity through localization: functional genomics reveals a role for the lysine acetyltransferase NuA4 and sphingolipid metabolism in regulating Acc1 activity and localization

Abstract: Acetyl-CoA Carboxylase 1 catalyzes the conversion of acetyl-CoA to malonyl-CoA, the committed step of de novo fatty acid synthesis. As a master regulator of lipid synthesis, acetyl-CoA carboxylase 1 has been proposed to be a therapeutic target for numerous metabolic diseases. We have shown that acetyl-CoA carboxylase 1 activity is reduced in the absence of the lysine acetyltransferase NuA4 in Saccharomyces cerevisiae. This change in acetyl-CoA carboxylase 1 activity is correlated with a change in localization.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 98 publications
0
8
0
Order By: Relevance
“…2017). NuA4 is also linked to sterol metabolism and eaf1Δ cells display increased accumulation of ergosterol esters (Pham et al . 2022).…”
Section: Resultsmentioning
confidence: 99%
“…2017). NuA4 is also linked to sterol metabolism and eaf1Δ cells display increased accumulation of ergosterol esters (Pham et al . 2022).…”
Section: Resultsmentioning
confidence: 99%
“…As a newly identified subunit of NuA4/TIP60 (Sudarshan et al, 2022), it is unclear if or how JAZF1 regulates enzymatic activity of the complex on or off chromatin. It is especially interesting that the role of NuA4/ TIP60 activity in transcription of metabolic genes and direct regulation of metabolic enzymes is well supported (van Beekum et al, 2008;Lin et al, 2009;Grönniger et al, 2010;Couture et al, 2012;Rossetto et al, 2014;Filteau et al, 2015;Jacquet et al, 2016;Dacquay et al, 2017;Rollins et al, 2017;Li et al, 2018;Cheng et al, 2019;Walden et al, 2020;Liu et al, 2021;Pham et al, 2022). Therefore, it is tempting to speculate that JAZF1 specifically modulates metabolism-related activity of the NuA4/ TIP60 complex.…”
Section: Discussionmentioning
confidence: 99%
“…First, while JAZF1 suppresses gluconeogenesis (Yuan et al, 2015;Zhou et al, 2020), NuA4/TIP60 is known to promote it (Lin et al, 2009). Second, JAZF1 has a pro-lipolytic anti-lipogenic function (Li et al, 2011;Ming et al, 2014b;Jang et al, 2014;Li et al, 2014;Wei et al, 2018), whereas NuA4/Tip60 was found to positively regulate either lipolysis or lipogenesis in different studies (Dacquay et al, 2017;Rollins et al, 2017;Li et al, 2018;Cheng et al, 2019;Wei et al, 2020;Liu et al, 2021;Pham et al, 2022). Lastly, JAZF1 stimulates the PI3K-Akt pathway downstream of insulin signaling (Yuan et al, 2015;Zhou et al, 2020), but NuA4/TIP60 was found to suppress it (Lu et al, 2011;Yang et al, 2017;Zhang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations